2019
DOI: 10.1177/1363461519890435
|View full text |Cite
|
Sign up to set email alerts
|

Metaphors and cultural narratives on adaptive responses to severe adversity: A field study among the Indigenous Pitaguary community in Brazil

Abstract: The expressions resilience and posttraumatic growth represent metaphorical concepts that are typically found in Euro-American contexts. Metaphors of severe adversity or trauma and the expressions of overcoming it vary across cultures—a lacuna, which has not been given much attention in the literature so far. This study aimed to explore the metaphorical concepts that the Indigenous Pitaguary community in Brazil uses to talk about adaptive and positive responses to severe adversity and to relate them to their so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 61 publications
0
6
0
1
Order By: Relevance
“…The data sources presented herein originated from four separate data collections, which are part of a larger qualitative project that uses approaches from cultural clinical psychology and ethnography to explore metaphors related to extreme aversive events and catastrophic experiences and the ways these experiences can be overcome (Maercker & Heim, 2016;Meili, Heim, & Maercker, 2019;Rechsteiner, Tol, & Maercker, 2019). The main field studies were conducted with the indigenous communities of the Pitaguary from Monguba in the state of Ceará, Brazil, in July 2016 and the Adivasis from Pune, in Maharashtra, India, in November 2017.…”
Section: Participants and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The data sources presented herein originated from four separate data collections, which are part of a larger qualitative project that uses approaches from cultural clinical psychology and ethnography to explore metaphors related to extreme aversive events and catastrophic experiences and the ways these experiences can be overcome (Maercker & Heim, 2016;Meili, Heim, & Maercker, 2019;Rechsteiner, Tol, & Maercker, 2019). The main field studies were conducted with the indigenous communities of the Pitaguary from Monguba in the state of Ceará, Brazil, in July 2016 and the Adivasis from Pune, in Maharashtra, India, in November 2017.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…Like most of the indigenous people in Brazil today, the Pitaguary mainly speak Brazilian Portuguese and only use selected words from their native language, Tupí. The educational attainment of these participants ranged from 0 to 10 years, except for two participants who were about to obtain their university degrees (Meili et al, 2019).…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…The findings of this study partly support evidence from other qualitative studies from our own overarching research project exploring metaphorical expressions in other rural communities (see Rechsteiner, Maercker, Meili, & Heim, 2019). Similar concepts relating to primary embodied metaphors were also found in Brazil and Switzerland (Maercker & Heim, 2016;Meili et al, 2018;Meili, Heim, Pelosi, & Maercker, 2019;. Such universal metaphors can be described as archetypal qualities, reflecting a discourse of collective experiences (Jung, 1969).…”
Section: Discussionmentioning
confidence: 70%
“…The ethnologist Corina Salis Gross (University of Bern, Switzerland) discussed the topic of refugees in Switzerland and reported different views of psychological distress and their rich descriptions in narratives, referring to ‘nerves’ and ‘feeling nervous’ (Salis Gross ). Based on Kirmayer's approach of embodied and culturally contextualized metaphors, Iara Meili (University of Zurich, Switzerland) presented her field research with an indigenous community in Brazil (Meili, Heim, Pelosi & Maercker forthcoming). She examined metaphors on positive responses to severe adversities and reported that both universal and culturally specific metaphors could be identified.…”
Section: Content Of the Conferencementioning
confidence: 99%